2014
DOI: 10.7567/jjap.53.06je01
|View full text |Cite
|
Sign up to set email alerts
|

Detection of weak biological signal utilizing stochastic resonance in a GaAs-based nanowire FET and its parallel summing network

Abstract: We investigated biological signal detection utilizing stochastic resonance (SR) in a GaAs-based nanowire field-effect transistor (FET) and its parallel summing network. The SR phenomenon, in which the response to a weak signal is optimized by noise, was caused in the nanowire FET having a nonlinear transfer characteristic. We confirmed that the SR occurred on weak aperiodic electromyogram (EMG) signals induced on the surface of the forearm of a human subject. The EMG contaminated with intrinsic noise from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The EMG signals can be obtained by detecting the electrical potential generated by muscle cells when the muscle was contracted, thereby providing the information of the movement in human body. 30) For this reason, the application of EMG sensors is practical for diagnosing the medical issues of nerves and muscles such as muscles damage and neuropathy. The inset of Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The EMG signals can be obtained by detecting the electrical potential generated by muscle cells when the muscle was contracted, thereby providing the information of the movement in human body. 30) For this reason, the application of EMG sensors is practical for diagnosing the medical issues of nerves and muscles such as muscles damage and neuropathy. The inset of Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…There is an attempt to use stochastic resonance when detecting weak biological signals from the surface of the human body. By using a system of parallelized GaAs nanowire FETs, electromyography is obtained from the human upper arm via stochastic resonance phenomena with noise from living organisms [123]. It was reported that by utilizing biologically derived noise, signals with high SNR were succeeded in detection.…”
Section: Artificial System Using Noisementioning
confidence: 99%
“…26) We already confirmed that the SRbased technique can achieve a higher SNR than the conventional technique. 27) The purpose of this study is to investigate a robust EMG signal detection technique by combining SR and a flexible multiple surface electrode array to achieve both the increase in sensitivity and elimination of contact fluctuation. We introduce the novel use of carbon nanotube composite paper (CNT-cp) as the surface electrode material, which is flexible and easy to handle.…”
Section: Introductionmentioning
confidence: 99%